Effect of the p53–tristetraprolin–stathmin-1 pathway on trophoblasts at maternal–fetal interface - Ma, Xiao-Ling (PLoS One, 2017)
PROBLEM: To reveal the effect of p53–tristetraprolin–stathmin-1 signaling on trophoblasts and recurrent spontaneous abortion (RSA). METHOD OF STUDY: Stathmin-1 (STMN1), p53, and tristetraprolin (TTP) expression in paraffin-embedded villus tissue was determined using immunohistochemistry. HTR-8/SVneo cells were treated with doxorubicin to activate p53; STMN1 and TTP levels were detected by quantitative reverse transcription–PCR and western blotting. Western blotting and immunofluorescence were used to investigate STMN1 expression after TTP overexpression or knockdown in HTR-8 cells. RESULTS: STMN1 was downregulated and p53 was upregulated in the villus tissue from patients with RSA. Doxorubicin decreased STMN1 expression but enhanced TTP expression in HTR-8 cells. In vitro, TTP overexpression inhibited STMN1 production; TTP knockdown promoted it. TTP downregulated STMN1 expression in trophoblasts by directly binding its 3ʹ untranslated region. CONCLUSIONS: TTP modulates trophoblast function and interacts with STMN1 and p53, and is related to pregnancy outcomes.